A benchmark model for low voltage distribution networks with PV systems and smart inverter control techniques. (September 2022) - Ibrahim, Ibrahim Anwar; Hossain, M.J.
Abstract: Unbalanced three-phase low-voltage distribution networks (LVDNs) modeling, optimization, and control are essential for enabling high photovoltaic (PV) penetration levels. Accordingly, a new case study is developed to show the gaps and challenges at different PV penetration levels in LVDNs. In this case study, the aim is to provide a better understanding of LVDNs' behavior in order to support the development and validation of the models and tools. Therefore, a reduction model is proposed to decrease the simulation time by lowering the number of buses in the IEEE European LV Test Feeder, with a negligible error. In addition, an OpenDSS-Julia interface is developed to demonstrate the effects of different PV penetration levels on the inverters' behavior, active power curtailment, and voltage level in LVDNs. Results are demonstrated concerning several limitations and challenges in using existing smart inverter control techniques, in terms of the inverters' behavior, active power curtailment, and the voltage level. These limitations and challenges include over-voltage issues using the constant power factor technique, high active power curtailment using the volt–watt technique, and high current flows in the network assets and poor power factors using the volt–var technique. In addition, state-of-the-art system models have not taken-into-account the modeling of uncertainty effects on the performance of PV modules. Similarly, such models have largely ignored the internal and standby losses in the inverter models. These neglected issues may lead to under- or over-estimation of the impacts of PV systems on LVDNs and inaccurate estimations of the network's ability to accommodate high PV penetration levels. Graphical abstract: Highlights: A benchmark model for PV systems and smart inverter control techniques is proposed. A reduced model of the IEEE European LV distribution system is set out. An OpenDSS-Julia interface to show the behavior of PV systems is developed. PV systems effects on low-voltage distribution networks are investigated. Merits and demerits of the existing smart inverter techniques are concluded.